Gincana astronômica para alunos do ensino fundamental inicial usando o aplicativo para smartphone: astronomia em casa - Sena, Marília de Queiroz (2020)
The Brazilian Astronomy and Astronautics Olympiad (OBA) emerged intending to develop science and aiming to spark the student's interest in the themes. The main idea of this thesis is to investigate the student’s perception of the OBA, checking the possible difficulties faced by them during their participation in the school Olympiad. This thesis presents a preliminary study through the application of an opinion questionnaire to the students of the fourth and fifth grades from the José Bessa fundamental school (Escola Municipal de Ensino Fundamental José Bessa), located in the city of Beberibe, State of Ceara, Brazil. The participants of this research took part in the Olympiads of 2019. After the survey, we performed a diagnostic study of the test applied in the school to identify the students’ difficulties. Based on the collected data, we could verify that students did present difficulties when solving some questions from the test. Before this problem, the next step of the research was the implementation of the school Astronomy Gymkhana. The school Gymkhana was carried out completely in a virtual format through the Web App Astronomia em casa, which is linked to digital platforms such as Google meet, Wordwall, and Whatsapp. During the school gymkhana, we approached the contents from the OBA edict using interactive methodologies that could spark in the student the desire to learn. At the end of the gymkhana, we applied an online mock test provided by the OBA website aiming to motivate and improve the quality of teaching of contents related to astronomy and astronautics as a way of subsequently obtaining satisfactory results. To conclude, a satisfaction questionnaire on the applicability of the Web App product was carried out. Thus, the use of the educational application fulfilled the objective and contributed to the learning process in a fun and enjoyable way